Therapeutic plan model for induction protocol of non-promyelocytic acute myeloid leukemia - MEDEIROS, JÔSEFFER WIANEY TRINDADE; MARTINS, BRUNA CRISTINA CARDOSO; ANDRADE, CINTHYA CAVALCANTE; SALES, DIANE SOUSA; LEITÃO, JOÃO PAULO DE VASCONCELOS; NÉRI, EUGENIE DESIREE RABELO (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Propose a treatment plan model for induction protocol of non- promyelocytic acute myeloid leukemia, focused on reducing the adverse events inherent to pharmacotherapy. An exploratory research using UpToDate® and Micromedex® databases of drug interactions, incompatibilities and adverse reactions related to the chemotherapeutic agents. The drugs analyzed were included in the induction protocol for acute myeloid leukemia and in the Pharmacotherapeutic Guide from a reference University Hospital in onco-hematology. The data were analyzed in detail from the technical point of view subsidizing the elaboration of a therapeutic plan model with the description of the principal cares and precautions associated with the use and ideal administration time for the drugs. 18 drug-drug interactions was identified and of these 83.3% (n = 15) have the potential for causing some adverse effect. As the outstanding incompatibilities, two have been identified, both physical and related to anthracycline daunorubicin. The most frequent adverse reactions was listed being myelosuppression with greater importance attached the use of cytarabine and followed by gastrointestinal effects. Already related to daunorubicin stands out with frequency greater than 10% such as abnormalities on electrocardiogram and alopecia. From the information obtained, was formulated a therapeutic plan model by means of a proposal with ideal administration time aiming to minimize the risks identified in the survey. The clinical pharmacist may signal through the proposed model care and precautions of conduct, increasing the team safety and promotes enhancing the quality of care provided to patients.